2023
DOI: 10.1021/jacsau.2c00569
|View full text |Cite
|
Sign up to set email alerts
|

Glycosaminoglycans: What Remains To Be Deciphered?

Abstract: Glycosaminoglycans (GAGs) are complex polysaccharides exhibiting a vast structural diversity and fulfilling various functions mediated by thousands of interactions in the extracellular matrix, at the cell surface, and within the cells where they have been detected in the nucleus. It is known that the chemical groups attached to GAGs and GAG conformations comprise “glycocodes” that are not yet fully deciphered. The molecular context also matters for GAG structures and functions, and the influence of the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 165 publications
0
32
0
Order By: Relevance
“…However, work using heparan sulfate (HS) as a chemokine inhibitor could help explain the unexpected chemorepulsion activity of PSS. HS is a highly sulfated, long-chain polysaccharide that is an essential cofactor in the binding and activation of cell surface chemokine receptors. Recently, there has been interest in using HS mimetics to reduce inflammation and cancer metastasis by regulating chemokine activity. , Two HS mimetics (both highly sulfated tetrasaccharides) showed strong binding to MCP-1. , Both HS mimetics reduced breast cancer cell proliferation and inhibited MCP-1 induced chemotaxis. , Researchers performed Boyden chamber migration assays to compare MCF-7 cell migration in the presence of no chemoattractant (negative control), only chemoattractant (positive control), and chemoattractant plus HS mimetic (treatment). Notably, HS mimetics not only completely masked the chemoattractant-induced migration but caused fewer cells to migrate in the treatment condition than in the negative control containing no chemoattractant, similar to the effect observed in this work. , While the cause of this apparent HS mimetic chemorepellent effect is not further explored, it is suspected that a similar phenomenon could be occurring in the current system due to the chemical similarity of the highly sulfated polyelectrolyte PSS to the HS mimetics.…”
Section: Resultsmentioning
confidence: 99%
“…However, work using heparan sulfate (HS) as a chemokine inhibitor could help explain the unexpected chemorepulsion activity of PSS. HS is a highly sulfated, long-chain polysaccharide that is an essential cofactor in the binding and activation of cell surface chemokine receptors. Recently, there has been interest in using HS mimetics to reduce inflammation and cancer metastasis by regulating chemokine activity. , Two HS mimetics (both highly sulfated tetrasaccharides) showed strong binding to MCP-1. , Both HS mimetics reduced breast cancer cell proliferation and inhibited MCP-1 induced chemotaxis. , Researchers performed Boyden chamber migration assays to compare MCF-7 cell migration in the presence of no chemoattractant (negative control), only chemoattractant (positive control), and chemoattractant plus HS mimetic (treatment). Notably, HS mimetics not only completely masked the chemoattractant-induced migration but caused fewer cells to migrate in the treatment condition than in the negative control containing no chemoattractant, similar to the effect observed in this work. , While the cause of this apparent HS mimetic chemorepellent effect is not further explored, it is suspected that a similar phenomenon could be occurring in the current system due to the chemical similarity of the highly sulfated polyelectrolyte PSS to the HS mimetics.…”
Section: Resultsmentioning
confidence: 99%
“…GAGs are mainly located in the extracellular matrix. Although they were once thought of as a kind of inert glue around cells, recent research has shown that GAGs play a vital role in building biological systems and the transduction of biological signals in cell proliferation, regeneration, lipid metabolism, angiogenesis, and metastasis. , All these processes are mediated through their direct interactions with diverse protein targets such as collagens, chemokines, cytokines, growth factors, antithrombin, and cell adhesion molecules, which makes them essential players in cell biology. …”
Section: Introductionmentioning
confidence: 99%
“…Although they were once thought of as a kind of inert glue around cells, recent research has shown that GAGs play a vital role in building biological systems and the transduction of biological signals in cell proliferation, regeneration, lipid metabolism, angiogenesis, and metastasis. 14,15 All these processes are mediated through their direct interactions with diverse protein targets such as collagens, chemokines, cytokines, growth factors, antithrombin, and cell adhesion molecules, which makes them essential players in cell biology. 16−20 The participation of GAGs in physiological, pathological, or therapeutic functions results principally from their unique physicochemical and structural features, including high negative charge, high viscosity, lubricative properties, periodicity, unbranched polysaccharide structures, low compressibility, and the ability to attract and absorb enormous amounts of water.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hyaluronan (HA) is a naturally occurring non-sulfated glycosaminoglycan (GAG), cell-surface-associated biopolymer, and is the crucial component of tissue extracellular matrix (ECM). The chemical and structural characterization of GAGs is still a matter of intensive development [ 1 ]. HA is a regular polymer of disaccharides composed of glucuronic acid and N-acetylglucosamine linked via alternating β-1,4 and β-1,3 glycosidic bonds ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%